Potential exploitation reserves of middle - upper Pleistocene aquifer (qp2-3) in Ca Mau province - Thu, Trinh Hoai; Hoang, Nguyen Van; Huong, Tran Thi Thuy (Vietnam Journal of Marine Science and Technology, 2019)
The paper presents the results of evaluating and determining the potential exploitation reserves of groundwater in Ca Mau province. In particular, the study has identified the regional hydrogeological parameters, assessed potential exploitation reserves of groundwater, forecasted water level fluctuations, determined quantities of groundwater supply from the sea and from rainwater according to space and time, and detailedly established input parameters and boundary value for hydrogeological modelling. Calculation results show that the total potential reserves of qp2-3 aquifer is 1,924,111 m3 per day, in which the fresh water is 1,072,145 m3 per day (accounting for 55.7%) and the salt water is 623,067 m3 per day (accounting for 44.3%).